Antibacterial Activity of Ethanol Extract from Chromolaena odorata L. Against Staphylococcus aureus Bacteria - Reski Anti; Jabes W. Kanter; Wilmar Maarisit; Reky R. Palandi; Nancy C. Pelealu; Friska M. Montolalu (Biofarmasetikal Tropis (The Tropical Journal of Biopharmaceutical), 2025)
Chromolaena odorata L. has bioactive compounds that can be used as raw medicine materials. Bioactive compounds from Chromolaena odorata L. are reported to have pharmacological and antibacterial properties. This study aims to  the antibacterial activity. The antibacterial activity testing used the agar diffusion method using paper discs with 25, 50, 75, 100, and 125 µg/disc extract concentrations. Based on the results obtained, the ethanol extract of Chromolaena odorata L. has antibacterial activity of S. aureus with inhibition zone diameters of 12.14, 11.99, 12.63, 12.62, and 13.85 mm.